Dry Leaf-Composting Using M-Bio Activator: A Training Program for Senior High School Students in Ciamis - Endang Surahman; Eko Sujarwanto; Rifa’atul Maulidah; Ifa Rifatul Mahmudah; Galih Ramadhan; Rahma Nurul Putri; Revanika Yusman Bhinekas (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Education on waste management during the Limited face to Face Learning needs to emphasize more to school residents. Schools environments with lots of trees produce a lot of dry leaf organic waste. The solution related to this issue is to eliminate dry leaf organic waste with the least damaging effect on the environment and make it valuable. The innovation that can be offered is dry leaf composting using an M-BIO activator. Partners in this community service are students of SMAN 1 Baregbeg and SMAN 2 Ciamis. The method used is lectures, discussion, questions &answers, and training in composting practice. Based on the evaluation, 67% of the participants experienced increased knowledge about dry leaf organic waste composting. In addition, regarding the sustainability of independent composting, 83% of the participant were interested. The program opens up insights and changes participants' mindsets towards organic waste. In the future, this program will be school routine programs. Compost produced from students' practical activities during training and counseling can be used as plant fertilizer in school greening areas.